Suramin blocked hCAP18/LL-37-induced macrophage recruitment and M2 polarization to enhance the therapeutic efficacy of 1,25(OH)2D3 against hepatocellular carcinoma in vitro and in vivo mouse model - Zhang, Huidan; Xie, Wenjing; Duan, Wenliang; Yuan, Xueli; Yang, Yaxin; Chen, Qin; Zhu, Yiqiang; Chen, Yuqing (Frontiers in Nutrition, 2025)
Background1,25(OH)2D3 supplementation alone does not provide sufficient benefit to hepatocellular carcinoma (HCC) patients in clinical trials. Tumor-associated macrophages (TAMs)-mediated immunosuppression is regarded as a major hurdle for the effectiveness of several treatments. Previous studies revealed that hCAP18/LL-37 was an important factor which directly suppresses the anticancer activity of 1,25(OH)2D3 on HCC cells. However, whether TAMs contribute to the limited clinical efficacy of 1,25(OH)2D3 through hCAP18/LL-37 remains unclear.MethodsCo-culture systems of HCC cells (PLC/PRF-5, Huh7) with THP-1-derived macrophages and co-xenograft mouse models were established. Anticancer activity was evaluated in vitro and in vivo mouse models using standard assays. Mechanistic investigations utilized qRT-PCR, Western blot, flow cytometry, ELISA, and immunohistochemistry. Therapeutic efficacy of 1,25(OH)2D3/suramin combination was assessed in co-xenograft and N-Nitrosodiethylamine (DEN)/Carbon tetrachloride (CCl4)-induced HCC models.Results1,25(OH)2D3 (200–500 nM) promoted macrophage recruitment, M2 polarization, Akt/mTOR signal and STAT3 signal activation in HCC/macrophage co-culture systems. This effect was mediated by 1,25(OH)2D3-induced hCAP18/LL-37 overexpression, which facilitated TAM infiltration and M2 reprogramming. Suramin, a potent LL-37 inhibitor, abrogated these immunosuppressive effects by blocking LL-37 internalization, restoring M1 polarization and suppressing Akt/mTOR and STAT3 pathways. Notably, 1,25(OH)2D3/suramin combination therapy synergistically inhibited HCC proliferation, colony formation, and invasion in vitro. In xenograft models and DEN/CCl4-induced HCC models, suramin enhanced 1,25(OH)2D3’s efficacy by promoting M1 polarization, increasing intratumoral M1/M2 ratios, reducing tumor growth, and diminishing macroscopic nodules.ConclusionThe 1,25(OH)2D3-LL-37-TAM axis drives immunosuppression in HCC by modulating macrophage phenotypes. While suramin potently disrupts this axis, blocking LL-37-mediated TAMs recruitment and M2 polarization, while promoting antitumor M1 phenotype responses. These findings highlight suramin as a promising adjunct to 1,25(OH)2D3-based immunotherapy for HCC.